2022
DOI: 10.3389/fonc.2022.848107
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin-3-Gallate (EGCG) Modulates the Composition of the Gut Microbiota to Protect Against Radiation-Induced Intestinal Injury in Mice

Abstract: The high radiosensitivity of the intestinal epithelium limits the outcomes of radiotherapy against abdominal malignancies, which results in poor prognosis. Currently, no effective prophylactic or therapeutic strategy is available to mitigate radiation toxicity in the intestine. Our previous study revealed that the green tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) attenuates radiation-induced intestinal injury (RIII). The aim of the present study was to determine the effect of EGCG on the intestinal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…According to a rodent study, the green tea polyphenol (−)-epigallocatechin-3-gallate (EGCG) was found to protect against RE by increasing the ratio of Firmicutes/ Bacteroidetes and the abundance of probiotics, thereby reverting gut dysbiosis. 145 Zhang et al found that urolithin A (UroA) improved intestinal cell regeneration, which was primarily accomplished through the restoration of the intestinal bacterial profile. 146 Li et al found that butyrate attenuated RE via the activation of G protein-coupled receptors (GPCRs) and the restoration of the intestinal bacterial composition.…”
Section: Othermentioning
confidence: 99%
See 1 more Smart Citation
“…According to a rodent study, the green tea polyphenol (−)-epigallocatechin-3-gallate (EGCG) was found to protect against RE by increasing the ratio of Firmicutes/ Bacteroidetes and the abundance of probiotics, thereby reverting gut dysbiosis. 145 Zhang et al found that urolithin A (UroA) improved intestinal cell regeneration, which was primarily accomplished through the restoration of the intestinal bacterial profile. 146 Li et al found that butyrate attenuated RE via the activation of G protein-coupled receptors (GPCRs) and the restoration of the intestinal bacterial composition.…”
Section: Othermentioning
confidence: 99%
“…In recent years, a number of new radiation protection agents have been explored in basic research. According to a rodent study, the green tea polyphenol (−)‐epigallocatechin‐3‐gallate (EGCG) was found to protect against RE by increasing the ratio of Firmicutes/Bacteroidetes and the abundance of probiotics, thereby reverting gut dysbiosis 145 . Zhang et al.…”
Section: Modification Of Gut Microbiota and Re Managementmentioning
confidence: 99%
“…For example, epigallocatechin-3-gallate (EGCG; a major catechin in green tea) promotes the growth of beneficial Bacteroides and Bifidobacterium and suppresses the bloom of pathogenic Fusobacterium, Bilophila, and Enterobacteriaceae [186]. Such microbiota-modulating effects of EGCG are noted to protect against colitis [187], high-fat diet-induced obesity [188][189][190], radiation-induced mucositis [191], and Clostridium difficile infection (CDI) [192] in mice. Though how EGCG impacts the microbiota is not well understood, several studies propose that it could be due to the bactericidal effects of EGCG, i.e., (i) generating H2O2 that damages the bacterial cell wall [193,194], (ii) inhibiting bacterial fatty acid and folate biosynthesis [195,196], and (iii) inducing oxidative stress and reactive oxidative species (ROS) formation in susceptible bacteria [197].…”
Section: Dietary Polyphenolsmentioning
confidence: 99%
“…Urolithin A (UroA), a metabolite of the ellagitannin gut microbiota, can significantly reduce radiation-induced enterocyte apoptosis and improve the intestinal morphological structure and enterocyte regenerative capacity in irradiated mice [ 172 ]. Cai et al [ 173 ] reported that the green tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) could reverse the intestinal microbiota disorder caused by radiation, such as normalizing the ratio of Firmicutes / Bacteroidetes and increasing the abundance of beneficial bacteria. In addition, EGCG has been proven to alleviate radiation-induced intestinal injury (RIII).…”
Section: Radiotherapy For Cancer Based On the Gut Microbiotamentioning
confidence: 99%